The Impact of ICT Projects on Developing Economies: The Case of People with Physical Disabilities in Nigeria - Iliya, Abdulrashid Abubakar; Ononiwu, Chidi Gerald; Kah, Muhammadou M.O (The Impact of IC The Impact of ICT Projects on De ojects on Developing E eloping Economies: The Case conomies: The Case of People with Physical Disabilities in Nigeria, 2021)
This study investigates the use of computers by People with Disabilities (PWDs) and whether it improves capability and human development in sub-Saharan Africa. Based on a case study’s findings and interviews with PWDs, we build on the Technology-Augment Capability Approach to show how computers as technical objects and caregivers as non-technical objects facilitate four key capabilities for PWDs, namely (1) Capability to education, (2) Capability to socio-economic activities, (3) Capability to social relations, (4) Informational capabilities and capability to employment. However, PWDs’ ability to convert the use of computers into capabilities is influenced by conversion factors, such as personal, social, environmental, technological, choice, and agency. Furthermore, our findings show also that there are enabling factors, such as accessibility, technological know-how, computer features, and Internet connectivity which facilitate PWDs’ achieved functionings.
Keywords: ICT4D; computers; capability approach; people with disabilities; case study; Nigeria; Digital Development; ACE: Technology Enhanced Learning; ACETEL; National open university of Nigeria (NOUN); Olumide Babatope Longe